2001
DOI: 10.1046/j.1440-1843.2001.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteral feeding in stable chronic obstructive pulmonary disease patients

Abstract: There was a slight increase in weight and in pulmonary function in both groups but these results did not differ significantly. Possible formula contamination was confirmed. Furthermore, in the overall assessment, the physician and patients rated both formulas as comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…3,16,24 The BLEND 3 study found that children needed 1.5-fold energy and an adult study showed that 1.2-fold energy was required on BTFs, in comparison to CFs, to sustain growth. 24 A 1.5fold increase is likely needed in children, compared to a 1.2fold increase in adults, as children require more energy to grow. Pentiuk et al 16 found that children receiving BTFs initially lost weight despite intaking similar energy as when they were receiving CFs but met growth goals with close dietetic monitoring (Table 2).…”
Section: Growth and Nutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,16,24 The BLEND 3 study found that children needed 1.5-fold energy and an adult study showed that 1.2-fold energy was required on BTFs, in comparison to CFs, to sustain growth. 24 A 1.5fold increase is likely needed in children, compared to a 1.2fold increase in adults, as children require more energy to grow. Pentiuk et al 16 found that children receiving BTFs initially lost weight despite intaking similar energy as when they were receiving CFs but met growth goals with close dietetic monitoring (Table 2).…”
Section: Growth and Nutritionmentioning
confidence: 99%
“…Studies evaluating the energy and nutrition sufficiency of BTFs have produced mixed results (Table 2). 22,23 There is some evidence that increased energy intake is required to maintain growth in patients receiving BTFs 3,16,24 . The BLEND 3 study found that children needed 1.5‐fold energy and an adult study showed that 1.2‐fold energy was required on BTFs, in comparison to CFs, to sustain growth 24 .…”
Section: Growth and Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine original research studies met the review inclusion criteria. They consisted of two control trials, 27,28 one open-label clinical trial, 29 two retrospective cohort studies, 30,35 two cross-sectional studies, 31,32 and two open-label pilot studies. 5,33 Five studies 5,[31][32][33]35 were conducted with patients in the home setting with varying degrees of clinical oversight, and four were conducted with hospitalized patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…15 When poor growth has been noted, research has supported that inadequate weight gain was remedied with intervention to include increasing caloric intake and close follow-up from the registered dietitian nutritionist (RDN). 12 Two studies have reported the need for increased calorie intake on BTF compared with CEF to maintain a stable body mass index, 18,14 although Gallagher and colleagues also noted an increase in total body fatness using triceps skinfold measurements of children on BTF and suggested that calorie needs may not have been as high as previously thought. 14 Survey results by Johnson and colleagues found that parents of GT-fed children reported meeting growth goals more often with BTF than CEF.…”
Section: Growth and Weight Maintenancementioning
confidence: 99%